2017
DOI: 10.1007/s11096-017-0435-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving communication of medication changes using a pharmacist-prepared discharge medication management summary

Abstract: Background Discontinuity of care between hospital and primary care is often due to poor information transfer. Medication information in medical discharge summaries (DS) is often incomplete or incorrect. The effectiveness and feasibility of hospital pharmacists communicating medication information, including changes made in the hospital, is not clearly defined. Objective To explore the impact of a pharmacist-prepared Discharge Medication Management Summary (DMMS) on the accuracy of information about medication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Failure to mention changes makes it difficult for the primary care physician to know whether they were intentional or accidental, and failure to explain the reasons for medication changes makes it difficult for them to know whether to re-start a ceased medication, whether to continue a new medication, whether to titrate the dose, what the treatment goal is and what outcomes to monitor. This is particularly relevant in cases where the reason(s) may not be obvious [24].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Failure to mention changes makes it difficult for the primary care physician to know whether they were intentional or accidental, and failure to explain the reasons for medication changes makes it difficult for them to know whether to re-start a ceased medication, whether to continue a new medication, whether to titrate the dose, what the treatment goal is and what outcomes to monitor. This is particularly relevant in cases where the reason(s) may not be obvious [24].…”
Section: Discussionmentioning
confidence: 99%
“…Yet this pharmacist-generated information is not routinely shared with primary care physicians. A study by Ooi et al [24] reported that the option to receive a pharmacist-prepared summary of medication changes made in the hospital was an approach that many primary care physicians preferred and were satisfied with. In our study, when pharmacists contributed to discharge summaries, around 80% of clinically significant medication changes were stated in the EDS, and around two-thirds were both stated and explained.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations